Hyperammonemic Coma in an Adult due to Ornithine Transcarbamylase Deficiency - Daniel L. Roberts; David A. Galbreath; Bhavesh M. Patel; Timothy J. Ingall; Amer Khatib; Daniel J. Johnson (Case Reports in Critical Care)
Objective. To report an unusual cause of coma in an adult. Design. Case report. Setting. University teaching hospital. Patient. A previously healthy 53-year-old man initially presented with altered mental status and progressed to coma. He was found to be substantially hyperammonemic and did not improve with lactulose therapy and continuous venovenous hemodialysis. Results. Biochemical testing revealed previously undiagnosed ornithine transcarbamylase deficiency, and the patient responded to arginine, sodium phenylacetate, and sodium benzoate. Conclusion. Even in adult patients with no known history, inborn errors of metabolism must be considered in the differential diagnosis of unexplained coma. Defects of the urea cycle can present with an unprovoked hyperammonemic coma.